Mapping Environmental Engagement: Risks and Opportunities of Eco-Emotions - Currat, Antoine (International Transitions, 2026)
The French population demonstrates strong awareness of the ecological crisis, yet this does not fully translate into behaviours aligned with climate objectives. Despite broad public support for environmental policies, the most impactful individual actions remain marginal, while a minority but stable form of climate scepticism persists. Recent research shows that emotions—particularly "eco-emotions"—play a central role in ecological engagement, going beyond cognitive rationality alone. The concept of "eco-consciousness" is introduced to connect emotions, environmental knowledge, and behaviours. The study highlights non-linear individual trajectories, marked by phases of cognitive shock, emotional overload, and subsequent regulatory action. Eight ecoconscious profiles are identified, ranging from the Climate Sceptic to the Positive, including the Lost, the Angry, and the Paralysed. Each presents specific needs in terms of support and intervention. An operational typology is proposed to guide actions carried out with individuals, organisations, and public institutions. Unpleasant eco-emotions carry significant risks for individuals (anxiety symptoms, isolation) and for organisations (disengagement, conflicts, burnout). Finally, the analysis underscores the opportunities offered by an appropriate mobilisation of emotions to foster ecological action.